Circadian rhythm in salivary melatonin in narcoleptic patients - Blažejová, Kateřina; Illnerová, Helena; Hájek, Ivan; Nevšímalová, Soňa (Neuroscience letters, 2008)
Narcolepsy is characterized, beside other features, by excessive daytime sleepiness and disturbed sleep at night. The pineal hormone melatonin may affect the sleep characteristics. The aim of the study was to compare the circadian rhythm in salivary melatonin in narcoleptic patients with that in control healthy subjects; 18 patients and 21 age- and gender-matched controls were involved. Narcoleptic patients exhibited a nocturnal increase in salivary melatonin similar to the one in control subjects. The morning melatonin decline in the narcoleptic group, as opposed to the control group was, however, not significant, as 8 out of 18 patients exhibited elevated melatonin levels also during the day. In these patients, the mean daytime value of the multiple sleep latency test (MSLT) was decreased when compared with that in patients with undetectable daytime melatonin levels. The results suggest that in some narcoleptic patients the circadian rhythm might be disturbed.
Keywords: cirkadiánní rytmus; Humans; lidé středního věku; dítě; melatonin; Child; Female; Narcolepsy; dospělí; financování organizované; Financing, Organized; lidé; narkolepsie; Biomarkers; Saliva; Circadian Rhythm; Chronobiology Disorders; Adult; biologické markery; ženské pohlaví; Male; Middle Aged; sliny; chronobiologické poruchy; mužské pohlaví; Melatonin